Bitcoin Sebagai Alat Investasi: (Analisis Hasil Keputusan Bahtsul Masail Ma’had Aly Hasyim Asy’ari Tebuireng tahun 2018 Tentang Bitcoin) - Rahman, Miftahur; Muhaini, Akhmad; Ubaidillah, Hasbi (MADINAH, 2020)
Bitcoin is a cryptographic-based digital commodity, also known as virtual currency or digital currency, which is used as a means of transactions and investments. In Indonesia the use of bitcoin is not merely a matter of technology, but has entered the realm of fiqh. An interesting phenomenon related to this is the response of several Islamic organizations and also study forums at Islamic boarding schools in Indonesia in addressing the bitcoin issue. Among them is Bahtsul Masail, the Nahdlatul Ulama Regional Manager (PWNU) in East Java in 2018. According to Bahtsul Masail's decision on the fiqh view of the use of bitcoin as a transaction and investment tool, it is legal, and may be used for muamalah. This is different from the results of the bahtsul masail in Ma'had Aly Hasyim Asy'ari Tebuireng Jombang, that bitcoin is classified as a virtual asset like dain (accounts receivable). And can be used as a legal transaction tool. But if bitcoin is used as an investment tool then the law is haram because the bitcoin exchange rate is very volatile. Based on this background, a problem arises, namely how to analyze the decision of Bahtsul Masail Ma'had Aly Hasyim Asy'ari about bitcoin and use what method to view bitcoin. The type of research used is library research. Using a normative legal approach (doctrinal), then the research is presented using descriptive techniques. In bahtsul masail using the ijtihad jama'i and ijtihad tatbiqi methods, in bahtsul masail using the term ilhaq, based on evidence, that bitcoin is equated with speculation (gambling), it is illegal.